DEKOMPOSISI SERASAH DAUN Sonneratia alba DAN ANALISIS UNSUR HARA C N DAN P DI PERAIRAN DESA SEI SAKAT KECAMATAN PANAI HILIR KABUPATEN LABUHAN BATU PROVINSI SUMATERA UTARA - Ratna Dewi; Yunasfi Djayus; Amanatul Fadhilah (AQUACOASTMARINE, 2018)
Mangrove leaves have decomposition process that gives donation of organic material is a source of food for various types of biota, other organisms in mangrove ecosystem. The objectives of this study were to count the decomposition rate of Sonneratia alba litter at each station, and count the percentage of carbon nutrient content (C), Nitrogen (N), Phosphorus (F) and C / N Ratio at each station location. The research was conducted in Sei Sakat Village, Panai Hilir Sub-district, Labuhan Batu District, North Sumatera Province conducted from March to May 2017. The research station was determined by purposive sampling method at three stations with station determination based on the availability of Sonneratia alba mangrove type in Sei Sakat Village. The results showed that the decomposition rate decreased the highest litter weight of station I (30,09 g/day) while the lowest station III (7,272 g/day). Carbon (C) content during the 90 days carbon-highest decomposition process of station III (18,80%) while the lowest station I (14,87%). Nitrogen (N), the highest station nitrogen day I and III (2,95%) while lowest station II (2,50%) and Phosphorus (P), the highest Phosphorus station III (0,29%) while lowest station I (0,20%)while the ratio of C/N during peroses decomposition of 90 days that is the highest ratio of station II (7,009%).Kata kunci : Dekomposisi, Analisis unsur hara, Daun Sonneratia alba.